Legal Protection of Patients in Clinical Teleconsultation Service Practice in Indonesia - M. Altef Dasril; Erni Herdiani (CV. Norma Global, 2025)
The development of digital technology is growing rapidly, as well as in the world of health. At first, Telemedicine was limited to only among Health Service Facilities as a solution to the challenge of the limited number of specialist/subspecialist doctors at Remote Hospitals in the country. However, after the COVID-19 Pandemic struck, the development of Telemedicine grew rapidly. This needs serious attention, especially in the aspect of legal protection. If the status of the COVID-19 Pandemic is revoked, how will the Legal Arrangements for Clinical Teleconsultation services be? How is Patient Legal Protection in the Practice of Clinical Teleconsultation Services? Methods This research uses a normative juridical method with an inductive conclusion approach. The result is that the existing legal regulation of Clinical Teleconsultation is only limited to the pandemic period and has many things that need to be addressed in its implementation and supervision, especially in terms of protection of patient rights in compliance with the rules and legislation that apply. The government needs to start drafting detailed regulations right away to ensure that patients using clinical teleconsultation services are protected by the law. Especially related to licensing and supervision.